The Sp1-Responsive microRNA-15b Negatively Regulates Rhabdovirus-Triggered Innate Immune Responses in Lower Vertebrates by Targeting TBK1 - Chang, Renjie; Chu, Qing; Zheng, Weiwei; Zhang, Lei; Xu, Tianjun (Frontiers in Immunology, 2021)
As is known to all, the production of type I interferon (IFN) plays pivotal roles in host innate antiviral immunity, and its moderate production play a positive role in promoting the activation of host innate antiviral immune response. However, the virus will establish a persistent infection model by interfering with the production of IFN, thereby evading the organism inherent antiviral immune response. Therefore, it is of great necessity to research the underlying regulatory mechanisms of type I IFN appropriate production under viral invasion. In this study, we report that a Sp1–responsive miR-15b plays a negative role in siniperca chuatsi rhabdovirus (SCRV)-triggered antiviral response in teleost fish. We found that SCRV could dramatically upregulate miiuy croaker miR-15b expression. Enhanced miR-15b could negatively regulate SCRV-triggered antiviral genes and inflammatory cytokines production by targeting TANK-binding kinase 1 (TBK1), thereby accelerating viral replication. Importantly, we found that miR-15b feedback regulates antiviral innate immune response through NF-κB and IRF3 signaling pathways. These findings highlight that miR-15b plays a crucial role in regulating virus–host interactions, which outlines a new regulation mechanism of fish’s innate immune responses.